Biodegradable Zn−1wt.%Mg(−0.5wt.%Mn) Alloys: Influence of Solidification Microstructure on Their Corrosion Behavior - Vida, Talita (2023)
The development of biodegradable Zn-based alloys for implants that effectively mimic the functionality of native bone throughout the healing process is a multifaceted challenge; this is particularly evident in the task of achieving appropriate corrosion rates. This work explores the incorporation of 0.5wt.%Mn into a Zn−1wt.%Mg alloy, with focus on the relationship between corrosion behavior and microstructure. Electrochemical corrosion tests were carried out in a 0.06 M NaCl solution using as-solidified samples with two distinct microstructural length scales. Mn addition was found to induce significant electrochemical active behavior. Localized corrosion was predominant in interdendritic regions, with the ternary alloy exhibiting a higher susceptibility. For both alloys, the coarsening of the microstructure promoted a slight inclination to accelerate the corrosion rates in both biodegradable Zn alloys. The corrosion rate showed an increase of about nine-times with Mn addition for coarser eutectic spacings, while for finer ones, the increase was by about 22 times.